2011
DOI: 10.1080/03602559.2011.553870
|View full text |Cite
|
Sign up to set email alerts
|

Surface Modification and Vapor-Induced Response of Poly(Vinylidene Fluoride)/Carbon Black Composite Conductive Thin Films

Abstract: A novel polymer sensing film was prepared by filling carbon blacks (CBs) into alkali-treated poly(vinylidene fluoride) (PVDF) matrices under ultrasonication. The microstructure, thermoproperties and crystalline behavior were investigated by FTIR, WAXD and DSC. The percolation behavior and vapor-induced response were examined, and the relationship between structure and response was elucidated. The results indicated that the reaction occurred in non-crystal regions, and had no effect on the crystal region and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…In addition, the morphology of a polymer blend near the surface layer can differ from that of the bulk, a phenomenon that has been exploited in controlling surface properties. , Molecular weight has a significant effect on both the final morphology of polymer blends and the mobility of constituent molecules. The mobility of components is also a function of concentration, because droplets and dissolved molecules are governed by different driving forces. A lower-molecular weight ( M w ) component can migrate faster than a higher- M w component toward the polymer–air interface to reach the region of higher shear rates. ,, A good example of surface modification via polymer blending is the migration of a low- M w poly(methyl methacrylate) (PMMA) to the surface of a polystyrene (PS)–PMMA blend having a relatively high- M w PS. , Moreover, it has been suggested that the migration mechanism is based on the surface tension gradient and polymer additive …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the morphology of a polymer blend near the surface layer can differ from that of the bulk, a phenomenon that has been exploited in controlling surface properties. , Molecular weight has a significant effect on both the final morphology of polymer blends and the mobility of constituent molecules. The mobility of components is also a function of concentration, because droplets and dissolved molecules are governed by different driving forces. A lower-molecular weight ( M w ) component can migrate faster than a higher- M w component toward the polymer–air interface to reach the region of higher shear rates. ,, A good example of surface modification via polymer blending is the migration of a low- M w poly(methyl methacrylate) (PMMA) to the surface of a polystyrene (PS)–PMMA blend having a relatively high- M w PS. , Moreover, it has been suggested that the migration mechanism is based on the surface tension gradient and polymer additive …”
Section: Introductionmentioning
confidence: 99%
“…5,22,23 A good example of surface modification via polymer blending is the migration of a low-M w poly(methyl methacrylate) (PMMA) to the surface of a polystyrene (PS)−PMMA blend having a relatively high-M w PS. 24,25 Moreover, it has been suggested that the migration mechanism is based on the surface tension gradient and polymer additive. 26 When the system consists of two minor components, the complex morphology of ternary polymer blends may facilitate the migration of the minor components.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Lots of researches have reported the structure, rheological and mechanical properties of PVDF/ CNTs composites [29][30][31][32][33][34][35][36][37] . The crystallization behavior of PVDF/CNT composites has also been studied extensively and most researchers focused on the transition of α-phase to β-phase or the formation of β-phase PVDF crystals, because the plane zigzag conformation of CNTs facilitates the formation of β-phase PVDF crystals [38][39][40][41] .…”
Section: Introductionmentioning
confidence: 99%
“…is could be useful for improving their functional properties suitable for engineering applications [19]. It is reported that carbon-based nanofillers such as carbon black [20], CNTs [21], graphene, and graphene oxide [22] are suitable candidates with PVDF blending for the improvement of electrical conductivity, thermal conductivity, and dielectric constant of the material [23]. Moreover, such composite itself has self-lubricating properties which reduce the friction and guarantee security contra damage and distortion [24].…”
Section: Introductionmentioning
confidence: 99%